Teatro performativo queer: Scene fluide degli anni Dieci - Casi, Stefano (Mimesis Journal, 2021)
Four recent Italian theatrical works, created by Andrea Adriatico, Enzo Cosimi, Irene Serini and Motus, expose the potential of the development of performative theatre, thanks to the transfer of the queer theme also to the expressive codes and the modalities of representation: the fluidity of identity and orientation also ap-plies to the shows, which take on a fluid form. The essay explores these modali-ties through four perspectives: the «laterality» of the narrative, the crossing of theatrical genres, the «mutant» identity of the spectators, the relationship bet-ween personal and political discourse, also in reference to a classic of queer theatre, La traviata norma (1976).